Reversible splenial lesion syndrome in children: a retrospective study of 130 cases - Chen, Hui; Yu, Xiongying; Chen, Yong; Wu, Huaping; Wu, Zhuqiang; Zhong, Jianmin; Tang, Zhenyu (Frontiers in Neurology, 2023)
Background Reversible splenial lesion syndrome (RESLES) is a new clinico-radiological syndrome. We retrospectively analyzed the clinical features of 130 children with RESLES in China, which is the largest case series available in the literature. Methods The clinical data of children diagnosed as RESLES in Jiangxi Provincial Children's Hospital between 2017 and 2023 were retrospectively analyzed. The 130 cases were divided into two groups: ≤ 3 years old group (group A) (n = 83) and > 3 years old group (group B) (n = 47). The chi-squared test or Fisher's test was used to evaluate the data. Results The vast majority of patients (127/130 cases, 97.7%) had prodromal symptoms of infection. Preceding infections of the gastrointestinal tract were statistically more significant in group A (60/83, 72.3%) than in group B (11/47, 23.4%) (P < 0.05). Preceding infections of the respiratory tract were statistically more significant in group B (33/47, 70.2%) than in group A (17/83, 20.5%) (P < 0.05). Seizures were statistically more significant in group A (82/83, 98.8%) than in group B (24/47,51.1%) (P < 0.05). The disturbance of consciousness and headache/dizziness were statistically more significant in group B (27/47, 57.4%; 37/47, 78.7%) than in group A (3/83, 3.6%; 1/83, 1.2%), respectively (P < 0.05). Convulsions with mild gastroenteritis (CwG) were statistically more significant in group A (50/83, 60.2%) than in group B (8/47, 17.0%) (P < 0.05). However, encephalitis/encephalopathy was statistically more significant in group B (20/47, 42.6%) than in group A (10/83, 12.0%) (P < 0.05). MRI showed cytotoxic edema in typical locations (RESLES type-1 limited to the splenium of the corpus callosum and RESLES type-2 spread to the entire corpus callosum, adjacent white matter, or both). There was full recovery of the lesions of MRI in all cases from 3 days to 50 days after the initial examinations. All the children showed normal neurodevelopment. Conclusion Infection was the most common cause of RESLES. Infections of the gastrointestinal tract are common in ≤ 3 years old children, while infections of the respiratory tract are common in >3 years old children. Younger patients are more likely to develop convulsions, and older children were more likely to have symptoms with disturbance of consciousness and headache/dizziness. RESLES has characteristic MRI manifestations and a good prognosis.